H19-Promoter-Targeted Therapy Combined with Gemcitabine in the Treatment of Pancreatic Cancer. (3rd June 2012) - Sorin, Vladimir; Ohana, Patricia; Gallula, Jennifer; Birman, Tatiana; Matouk, Imad; Hubert, Ayala; Gilon, Michal; Hochberg, Avraham; Czerniak, Abraham
Abstract : Pancreatic cancer is the eighth cancer leading cause of cancer-related death in the world and has a 5-year survival rate of 1–4% only. Gemcitabine is a first line agent for advanced pancreatic therapy; however, its efficacy is limited by its poor intracellular metabolism and chemoresistance. Studies have been conducted in an effort to improve gemcitabine treatment results by adding other chemotherapeutic agents, but none of them showed any significant advantage over gemcitabine monotherapy. We found that 85% of human pancreatic tumors analyzed by in situ hybridization analyses showed moderated to strong expression of the H19 gene. We designed a preclinical study combining gemcitabine treatment and a DNA-based therapy for pancreatic cancer using a non viral vector BC-819 (also known as DTA-H19), expressing the diphtheria toxin A chain under the control of the H19 gene regulatory sequences. The experiments conducted either in an orthotopic and heterotopic pancreatic carcinoma animal model showed better antitumor activity following the sequential administration of the vector BC-819 and gemcitabine as compared to the effect of each of them alone. The results presented in the current study indicate that treatment with BC-819 in combination with gemcitabine might be a viable new therapeutic option for patients with advanced pancreatic cancer.